Cases of Acute Cholecystitis: A Clinical Study and Follow-Up (International Journal of Food and Nutritional Sciences, 2022)
Background and Objective: One of the most typical causes of acute abdomen is acute cholecystitis, which is characterized by gallbladder inflammation and typically results from cystic duct obstruction. The was aimed to study socio-demographical and clinical profile of diagnosed cases of Acute Cholecystitis.Methodology: The study was observational, prospective, and inferential study conducted among 60 adult patients (18 years and above) being referred to the Emergency department and Department of Surgery, Santosh Medical College and Hospital, Ghaziabad (Uttar Pradesh) presenting with Upper Abdominal Pain.Result: About 95% of the patients have calculus cholecystitis. Mean age of the study participant was 43.5) years. Study showed that majority of them were females (76.7%). In the present study also, pain was reported by all patients accompanied with fever by 40% and nausea vomiting by 65% patients.Conclusion: The prevalence of acute cholecystitis varies with age, sex and ethnic group. Ultrasonography remains the most important investigation of choice for the diagnosis of acute cholecystitis. The characteristic signs seen in ultrasound imaging include edema and thickening of the gallbladder wall, occasionally gas in the wall, and absence of visualization of the organ